The Problem of Defecting Facing The Qibla: An Analysis of The Understanding of The Hadith of Ali Mustafa Yaqub - Amanullah, Adhitama Alim (Afkaruna: Indonesian Interdisciplinary Journal of Islamic Studies, 2026)
This study examines the prohibition and permissibility of defecating while facing the Qibla, based on Ali Mustafa Yaqub's methodology of hadith interpretation. The central focus is the scholarly debate concerning this ruling, in which al-Nawawi's al-Majmu' records four distinct juristic positions. This article critically analyzes Yaqub's textual-contextual hermeneutical framework encompassing majaz (trope or figurative usage), ta'wil (allegorical interpretation), 'illah (ratio legis), and Arab socio-cultural context and situates it within the broader landscape of classical and contemporary hadith scholarship, including contributions from Yusuf al-Qaradawi, Muhammad al-Ghazali, and Jonathan A.C. Brown. The takhrij method is employed to trace hadith variants. The study argues that Yaqub's geographically inflected contextual approach makes a methodologically distinctive contribution, particularly in its application to non-Arabian Muslim contexts such as Indonesia. The results demonstrate that a dual textual and contextual reading is necessary for the accurate and contextually relevant application of prophetic traditions.